Biological activities of staphylococcal enterotoxin type A mutants with N-terminal substitutions. - Harris, T O (1995)
The purpose of this study was to examine the importance of certain N-terminal amino acid residues of staphylococcal enterotoxin type A (SEA) for biological activity. The results confirm our previous observation that Asn-25, Phe-47, and Leu-48 are important for SEA's emetic and superantigen activities. Substitutions at six other sites (Leu-12, Lys-14, Ser-16, Asp-45, Gln-46, and Thr-51) did not reveal any additional residues required for biological activity. Mutant SEAs with substitutions at 25, 47, or 48 all had decreased T-cell stimulatory activity, with the mutants at position 47 being the most defective. Results of a competition assay for binding to the major histocompatibility complex (MHC) class II-expressing cell line Raji suggested that the decreased superantigen activities of the mutants with substitutions at positions 47 and 48 are due to poor interactions with MHC class II molecules, whereas the defects of the mutants at position 25 are a consequence of faulty interactions with T-cell receptors. With respect to emetic activity in rhesus monkeys, the mutants at position 25 or 48 exhibited decreased but significant activity. Interestingly, the two mutants at position 47 had different emetic activities; SEA-F47G was nonemetic when administered intragastrically at 500 micrograms per animal, whereas SEA-F47S was emetic at this dosage. Since the mutants at position 47 were equally defective for superantigen activity, this further supports our previous suggestion of an incomplete correlation between SEA's emetic and superantigen activities.